UJI POTENSI TIGA VARIETAS JAGUNG DAN SAAT EMASKULASI TERHADAP PRODUKTIVITAS JAGUNG SEMI (BABY CORN) - Efrain - Patola; Sri - Hardiatmi (Innofarm:Jurnal Inovasi Pertanian, 2011)
Abstract The purpose of this research are (1) to known potency from three  variety of corn to be developed as baby corn, (2) to known influence of the emasculation moment to baby corn  productivity, and (3) to known influence of interaction  between the emasculation moment and variety to baby corn productivity The research compiled factorially use Randomized Completely Block Design (RCBD) which consist of 2 factors and 3 replications. Factor 1 is variety by 3 levels, and factor 2 is the emasculation moment by 3 level. The result of the research, are: (1) variety of King Sweet and Chia Tai  have potency  to be developed as a  baby corn variety, and require to be tested  more continue, (2) the emasculation at time  staminate  emerge  give influence  better to number of cob without husk per plant, and (3) the interaction between variety  with when emasculation  non significant  effect  to all observation component. Key word : variety, emasculation, productivity, and baby corn